MODERASI LEADER–LEADER EXCHANGE (LLX) PADA HUBUNGAN ANTARA TRANSFORMATIONAL LEADERSHIP DAN PSYCHOLOGICAL EMPOWERMENT - Surya Dharma; Ririn Handayani; Adolf Bastian; Didik Siswanto (Smart Education, 2026)
Abstract: Based on the perspective of Social Exchange Theory, this study aims to explore the moderating mechanism of Leader–Leader Exchange (LLX) in the relationship between Transformational Leadership and Psychological Empowerment. Although the relationship between transformational leadership and psychological empowerment has been extensively researched, the role of inter-managerial relationships (LLX) as a moderator within the leadership ecosystem environment still requires deeper empirical examination. This study employs a quantitative research design with hypothesis testing based on Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings confirm that transformational leadership is positively associated with psychological empowerment, and high-quality LLX relationships further strengthen the effectiveness of transformational leadership in enhancing subordinates' psychological capacity. This research provides theoretical contributions to the multi-level leadership literature and human resource management. Keyword: Transformational Leadership, Psychological Empowerment, Leader–Leader Exchange (LLX), Social Exchange Theory, PLS-SEM Abstrak: Berdasarkan perspektif Social Exchange Theory, penelitian ini bertujuan untuk mengeksplorasi mekanisme moderasi Leader–Leader Exchange (LLX) dalam hubungan antara Transformational Leadership dan Psychological Empowerment. Meskipun hubungan antara kepemimpinan transformasional dan pemberdayaan psikologis telah banyak diteliti, peran hubungan antar manajer (LLX) sebagai pemoderasi lingkungan ekosistem kepemimpinan masih memerlukan pengujian empiris yang lebih mendalam. Penelitian ini menggunakan desain penelitian kuantitatif dengan pengujian hipotesis berbasis regresi terinflasi atau Partial Least Squares (PLS-SEM). Hasil penelitian mengonfirmasi bahwa kepemimpinan transformasional berhubungan positif dengan pemberdayaan psikologis, dan keberadaan hubungan LLX yang berkualitas tinggi semakin memperkuat efektivitas kepemimpinan tersebut terhadap penguatan kapasitas psikologis bawahan. Penelitian ini memberikan kontribusi teoritis bagi literatur kepemimpinan bertingkat (multi-level leadership) dan manajemen sumber daya manusia. Kata kunci: Kepemimpinan Transformasional, Pemberdayaan Psikologis, Leader–Leader Exchange (LLX), Social Exchange Theory